2005
DOI: 10.1016/s0002-9440(10)62324-3
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β and Platelet-Derived Growth Factor Signal via c-Jun N-Terminal Kinase-Dependent Smad2/3 Phosphorylation in Rat Hepatic Stellate Cells after Acute Liver Injury

Abstract: After liver injury, transforming growth factor-beta (TGF-beta) and platelet-derived growth factor (PDGF) regulate the activation of hepatic stellate cells (HSCs) and tissue remodeling. Mechanisms of PDGF signaling in the TGF-beta-triggered cascade are not completely understood. TGF-beta signaling involves phosphorylation of Smad2 and Smad3 at linker and C-terminal regions. Using antibodies to distinguish Smad2/3 phosphorylated at linker regions from those phosphorylated at C-terminal regions, we investigated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
168
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(176 citation statements)
references
References 37 publications
7
168
0
1
Order By: Relevance
“…Immunohistochemical analyses were performed as described previously. 17 Primary antibodies used in this study included mouse monoclonal anti-␣SMA Ab (1.7 g/ml; DAKO, Glostrup, Denmark), mouse monoclonal anti-PAI-1 Ab (0.4 g/ml; Santa Cruz Biotechnology, Santa Cruz, CA), mouse monoclonal anti-p21 WAF1 Ab (0.5 g/ml; DAKO), in addition to rabbit polyclonal anti-pSmad3L (2 g/ml), and rabbit polyclonal antipSmad3C (0.5 g/ml) described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical analyses were performed as described previously. 17 Primary antibodies used in this study included mouse monoclonal anti-␣SMA Ab (1.7 g/ml; DAKO, Glostrup, Denmark), mouse monoclonal anti-PAI-1 Ab (0.4 g/ml; Santa Cruz Biotechnology, Santa Cruz, CA), mouse monoclonal anti-p21 WAF1 Ab (0.5 g/ml; DAKO), in addition to rabbit polyclonal anti-pSmad3L (2 g/ml), and rabbit polyclonal antipSmad3C (0.5 g/ml) described above.…”
Section: Methodsmentioning
confidence: 99%
“…13 We therefore have focused on Smad3 signaling, 14,15 and have recently reported different roles of Smad3 phosphoisoform-mediated signaling in epithelial cells and mesenchymal cells. 16,17 Thus, TGF-␤ activates not only TGF-␤ type I receptor (T␤RI) but also c-Jun N-terminal kinase (JNK), converting Smad3 into two distinctive phosphoisoforms: C-terminally phosphorylated Smad3 (pSmad3C) and linker-phosphorylated Smad3 (pSmad3L). 16 The T␤RI/pSmad3C pathway inhibits growth of epithelial cells including hepatocytes, whereas JNK/pSmad3L-mediated signaling promotes ECM deposition by activated mesenchymal cells such as hepatic stellate cells (HSCs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Although Smad2/3 signaling is relatively specific to the binding of ligands of the TGFb/activin family to cell surface receptors, investigators are discovering that MAPKs (p42/p44 Erk1/2, JNK, or p38MAPK) phosphorylate specific sites in the middle linker region of Smad2/3, sites that are distinct from the C-terminus that is phosphorylated by the TGFb II receptor (Figure 2). [33][34][35][36] Thus, ligands capable of activating MAPKs potentially modulate Smad signaling induced by TGFb. It has recently been demonstrated that p38MAPK activate phosphorylation of Smad3 in the middle linker region, which enhances Smad3/4 complex formation and nuclear translocation, 37 consistent with our finding of diminished Smad3/4 reporter gene activity in the presence of a p38MAPK inhibitor.…”
Section: Tgfb Signal Transductionmentioning
confidence: 99%
“…TGF-b-dependent JNK/pSmad3L oncogenic pathway activation has been observed in rat hepatic stellate cells and myofibroblasts after liver injury. 24,25 The status of the TGF-b-dependent JNK/pSmad3L oncogenic pathway can be used to evaluate the risk for developing hepatocellular carcinoma (HCC) in HBVinfected patients. 26 Based on the results of the gene expression analysis, TGF-b-dependent epithelial-mesenchymal transition (EMT) and cell proliferation occurred among the top 10 rankings (Fig.…”
Section: Gene Expression Analysis Of Iccmentioning
confidence: 99%